Pengaruh Atribut Destinasi Wisata dan Motivasi Wisatawan terhadap Minat Berkunjung Wisatawan pada Wisata Klakat Watubaing - Natalia Merlina (Jurnal CUAN Universitas Nusa Nipa Maumere, 2024)
This research aimed to (1) determine the influence of tourist destination attributes on tourist visiting interest in Klakat Watubaing tourist, (2) determine the influence of tourist motivation on tourist on tourist visiting interest in Klakat Watubaing tourist, and (3) determine the combined influence of tourist destination attributes and tourist motivation on tourist visiting interest in Klakat Watubaing tourist. The research design used descriptive and associative methods through a quantitative approach. The sample size was determined using the Slovin formula, resulting in 100 respondents from Klakat Watubaing tourist. Data were collected through questionnaires and analyzed using inferential statistics, specifically multiple linear regression. Hypothesis testing was conducted through the t-test and f-test. The results indicated that : (1) the tourist destination attributes variable (X1) had a significant effect on the visiting interest variable (Y) with a t-count value of 2.429 > 1.98, (2) the tourist motivation variable (X2) partially influenced visiting interest with a t-count value of 9.741 > 1.98, and (3) both tourist destination attributes and tourist motivation had a significant combined effect on tourist visiting interest at Klakat Watubaing tourist, as indicated by an F-value of 75.354 > 3.09.